The story of a bad boy - Aldrich, Thomas Bailey, 1836-1907 (Houghton, Mifflin and Co. ; Riverside Press, 1895)
These boyhood adventures of a mischievous lad in nineteenth-century New England are based on the author's own experiences. This "Northern man with Southern principles" was sent from New Orleans to Massachusetts to live with his grandfather.